The crack path in fuselage panel under mixed mode biaxial loading (Fracture and Structural Integrity, 2019)
This paper provides the background for practical applications of nonlinear fracture resistance parameters for structural integrity assessment of aviation structures with initial cracks. The subject of this numerical study is a fragment of airplane fuselage panel with initial central crack under biaxial loading. The plastic stress intensity factor (SIF) concept is here applied to estimate the critical crack size in fuselage panel under biaxial loading. The fracture damage zone influence on crack tip stress state in airplane fuselage panel under biaxial loading is evaluated. The values of plastic stress intensity factor Kp obtained from both elastic-plastic solution for isotropic body and elastic-plastic solution with cohesive zone are compared to the critical values of nonlinear fracture resistance parameter, for fuselage panel under biaxial loading. The curvilinear crack path in the considered fuselage panel under mixed mode biaxial loading is finally evaluated.
Keywords: Crack path; Mixed mode; Fuselage panel; Biaxial loading; Plastic stress intensity factor; Cohesive zone